Effective Website Accessibility Through Optimization Using Knapsack Programming Model (International Journal of Engineering and Computer Science, 2018)
Designing high efficient websites to facilitate effective webpage access has long been a challenge. A primary reason is that the web developers understanding of how a website should be structured can be considerably different from that of the users. While various methods have been proposed to relink webpages to improve accessibility using user access data, the completely reorganized new structure can be highly unpredictable, and the cost of disorienting users after the changes remains unanalysed. This paper addresses how to improve a website without introducing substantial changes. Specifically, we propose a mathematical programming model to improve the user access on a website while minimizing alterations to its current structure. Our model not only significantly improves the user access with very few changes, but also can be effectively solved. In addition, we define two evaluation metrics and use them to assess the performance of the improved website using the real data set. Evaluation results confirm that the user access on the improved structure is indeed greatly enhanced. More interestingly, we find that heavily disoriented users are more likely to benefit from the improved structure than the less disoriented users.